PAR 2021
DOI: 10.20517/2347-9264.2021.20
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint injection indocyanine green lymphography can reduce lymphaticovenular anastomosis surgical time and improve the surgical results for lymphedema

Abstract: injection indocyanine green lymphography can reduce lymphaticovenular anastomosis surgical time and improve the surgical results for lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…This will be seen as interrupted linear pattern in ICG lymphography. To allow ICG to re-enter the lymphatic channels and resume antegrade flow, it is injected anatomically proximal to such an area of linear pattern interruption [Figure 2] [9] .…”
Section: Discussionmentioning
confidence: 99%
“…This will be seen as interrupted linear pattern in ICG lymphography. To allow ICG to re-enter the lymphatic channels and resume antegrade flow, it is injected anatomically proximal to such an area of linear pattern interruption [Figure 2] [9] .…”
Section: Discussionmentioning
confidence: 99%
“…After 30 min of injection, the infrared imaging system of Photodynamic Eye (PDE, Hamamatsu Photonics, Japan) generated the subcutaneous ICG imaging. In the absence of evident lymphatic development, the multi-point injection mode 13 was used; four injection points were placed at the medial and lateral sides of the knee and the medial and lateral malleoli, respectively. In vitro irradiation using the infrared probe helped determine the patency of lymphatic vessels and mark their position (Figure 1(a)).…”
Section: Operative Techniquementioning
confidence: 99%
“…The calculation formula for the score of the Lymph-ICF-LL full scale and subscale is (the sum of the scores of the questions answered/the number of answered questions) × 10; hence, the score range of the full scale and each subscale is from 0 to 100. Five levels of lower limb lymphedema were identified using overall and subscale scores of Lymph-ICF-LL: no edema (score 0-4), mild edema (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), moderate edema (25-49), severe edema (50-95), and very severe edema (96-100). Research results have shown that Lymph-ICF-LL has good reliability and validity in both Chinese version 20 and other language versions.…”
Section: Lower Extremity Lymphedema Indexmentioning
confidence: 99%
“…In this minimally invasive imaging technique, indocyanine green (ICG), a fluorescent cyanine dye, is injected intradermally, and the flow and distribution of this dye in the body are analyzed using a near-infrared optical system. Further, because ICG molecules strongly bind to plasma proteins within the blood vessels and lymphatic vessels (LVs), they move along the blood and lymph fluid with few leakages out of the vessels 4 , 5 . Regarding optical properties, ICG molecules absorb infrared light between 600 and 900 nm, which has a 789 nm peak, and emit fluorescent light between 750 and 950 nm, which has an 814 nm peak 6 .…”
Section: Introductionmentioning
confidence: 99%